Shared Decision Making With Vulnerable Populations in the Emergency Department. (December 2016) - Castaneda‐Guarderas, Ana; Glassberg, Jeffrey; Grudzen, Corita R.; Ngai, Ka Ming; Samuels‐Kalow, Margaret E.; Shelton, Erica; Wall, Stephen P.; Richardson, Lynne D.
Abstract: The emergency department (ED) occupies a unique position within the healthcare system, serving as a safety net for vulnerable patients, regardless of their race, ethnicity, religion, country of origin, sexual orientation, socioeconomic status, or medical diagnosis. Shared decision making (SDM) presents special challenges when used with vulnerable population groups. The differing circumstances, needs, and perspectives of vulnerable groups invoke issues of provider bias, disrespect, judgmental attitudes, and lack of cultural competence, as well as patient mistrust and the consequences of their social and economic disenfranchisement. A research agenda that includes community‐engaged approaches, mixed‐methods studies, and cost‐effectiveness analyses is proposed to address the following questions: 1) What are the best processes/formats for SDM among racial, ethnic, cultural, religious, linguistic, social, or otherwise vulnerable groups who experience disadvantage in the healthcare system? 2) What organizational or systemic changes are needed to support SDM in the ED whenever appropriate? 3) What competencies are needed to enable emergency providers to consider patients' situation/context in an unbiased way? 4) How do we teach these competencies to students and residents? 5) How do we cultivate these competencies in practicing emergency physicians, nurses, and other clinical providers who lack them? The authors also identify the importance of using accurate, group‐specific data to inform risk estimates for SDM decision aids for vulnerable populations and the need for increased ED‐based care coordination and transitional care management capabilities to create additional care options that align with the needs and preferences of vulnerable populations.